Employee Performance Analysis Based on Competency and Work Experience in Hospital: - Tobing, May Suryati (International Journal Administration, Business & Organization, 2025)
This study provides a comprehensive overview of how employee competency and work experience collectively influence performance within hospital settings. Recognizing the critical role of human capital in ensuring high-quality patient care and organizational sustainability, this research addresses a gap by exploring the interplay of these factors rather than their isolated effects, specifically in Indonesian hospitals. Utilizing a library research method, the study synthesizes theoretical foundations and empirical findings from various scientific journals and relevant books. The analysis consistently reveals that both competency and work experience are significant determinants of employee effectiveness. Competency, encompassing technical skills, cognitive abilities, and behavioral attributes, directly enhances task execution and problem-solving. Work experience, conversely, contributes to operational maturity and practical judgment. Crucially, the findings highlight a synergistic interaction: optimal performance is achieved when strong competencies are reinforced by practical experience, while experience itself is most valuable when underpinned by continuous skill development. The study concludes that an integrated human resource strategy, emphasizing both competency development and experiential learning throughout an employee's career, is vital for sustaining high-quality hospital operations. This approach offers practical implications for refining recruitment, training, and promotion strategies to foster a highly effective healthcare workforce.